Prevalence, characteristics and risk factors of pressure ulcers in public and private hospitals care units and nursing homes in France. Issue 1 (1st January 2018) - Barrois, Brigitte; Colin, Denis; Allaert, François-André
ABSTRACT: Objective : The aim of this study conducted in 2014 was to describe the prevalence of pressure ulcers in different types of French hospital unit at the national level to compare them with data from the 1994 and 2004 study. Methods : This cross-sectional study was conducted over a single day. All care units were invited to participate by drawing lots stratified by region in successive waves until 1, 200 agreements were obtained. Lots were drawn for towns with more than 10, 000 inhabitants. All public- and private-sector hospital facilities in each town drawn by lot were invited to participate in the survey. Results : 776 hospital services throughout France took part and accommodated 21, 538 patients: 12, 752 women (59.2%) and 8, 786 men (40.8%). Of these patients, 1, 753 (8.1%; IC95% = 7.7; 8.5) had pressure ulcers. The pressure-ulcer rate was 7.8% (IC95% = [7.3; 8.3] (n = 997)) for hospitalized women and 8.6% (IC95% = [8.0; 9.2] (n = 756)) for men (p = 0.0381). The 8.1% level reported in 2014 therefore points to a reduction in pressure-ulcer prevalence; 8.6% in 1994 and 8.9% in 2004. Conclusions : The actions performed daily by healthcare professionals to prevent pressure ulcers, supported by research and training programs, including those by PERSE, are having a real impact over time.